ID 64 – Involvement of A-delta sensory fibres in amyotrophic lateral sclerosis. Issue 3 (March 2016) - Isak, B.; Tankisi, H.; Johnsen, B.; Pugdahl, K.; Brix Finnerup, N.; Brøgger Christensen, P.; Fuglsang-Frederiksen, A.
Abstract : Background: Amyotrophic lateral sclerosis (ALS), a neurodegenerative disease of upper and lower motor neurons, is considered to spare other neural systems. But, some neurophysiological and pathological studies showed sensory abnormalities in ALS. Objective: In this study, we wanted to evaluate the A-delta sensory fibres in ALS patients using laser evoked potentials (LEPs). Methods: We compared 15 definite-ALS patients and 27 healthy subjects, using Nd:YAP-LEPs. LEPs were evaluated based on N1, N2, P2 latencies, N1 amplitudes (baseline to peak), and N2P2 amplitudes (peak to peak) in upper (UE-) and lower (LE-) extremities. Results: ALS patients had longer UE-N2 (223.4 ± 31.3 ms vs. 204.55 ± 18.02 ms, P  = 0.002), LE-N2 (300.5 ± 40.4 ms vs. 269.03 ± 32.5 ms, P  = 0.01), and LE-P2 (418.7 ± 48.1 ms vs. 386.5 ± 36.8 ms, P  = 0.03) latencies than controls. Also, LE-N2P2 amplitudes were lower (12.4 ± 11.5 μV vs. 27.4 ± 12.1 μV, P  = 0.0003) in ALS patients than controls. UE- and LE-LEPs were abnormal in 5 and 7 ALS patients, respectively. Conclusions: The ALS patients showed considerable functional/structural impairment in A-delta fibres. Key message: ALS is a multisystem disorder. Detection of impairment in A-delta fibres should not rule out ALS diagnosis.